Analisis Kapasitas Ruang Parkir off Street di Pelabuhan Goto Sarimalaha - Tosofoe, Septhyani Putri; Muhammad, Amirudin Hi.; Altarans, Indra (Peneliti.net, 2025)
This study aims to analyze the off-street parking capacity and parking usage patterns at Goto Sarimalaha Port, Tidore Kepulauan City. As one of the main activity hubs for the local community, the port requires adequate parking facilities to accommodate vehicles during peak hours. The research employs a descriptive method, with data collected through field surveys, direct observations, and recording the number of vehicles entering and exiting the parking area at 15-minute intervals. The analysis includes parking accumulation, parking volume, parking turnover, parking index, parking duration, and parking space requirements. The results of the study show that the highest parking accumulation occurred on Thursday, 21 August 2025, reaching 85 vehicles, indicating that this day represents the peak usage period of the parking area. The parking index on several observation days also exceeded the available parking capacity, indicating that the current facilities are not yet sufficient to meet actual demand. Additionally, parking usage patterns tended to increase during ship arrival and departure times, causing significant accumulation spikes at certain intervals. Based on these findings, it is necessary to reorganize the parking layout, increase capacity, and improve vehicle circulation management to enhance the effectiveness and convenience of parking services at Goto Sarimalaha Port.